Tit Risk Evaluation of Land Transportation Users in Travel Safety - Jana Sandra Sandra; Ade Suryana; Yuliawan Yuliawan; Sunarmin Sunarmin (Sekolah Tinggi Ilmu Tarbiyah (STIT) Syekh burhanuddin, 2022)
Transportation problems on roads with high traffic density, along with the presence of road crime, are usually characterized by a high number of accidents. Road safety issues may even be categorized as cultural issues because of the far-reaching implications on our daily lives. The implementation of risk evaluation to run a road transport safety program has become a complex issue for it is not only related to technical challenges but also institutional, budgetary, government and community support which are closely connected to each other. Each region faces problems with unique characteristics, therefore road transportation safety programs are implemented differently according to the complexity of the problem. The findings of this study indicate that the implementation of traffic safety management programs needs to be effective. The conclusion is drawn on how much citizens consider the program beneficial to them and how much benefit from the implementation of the program is perceived. Although it is impossible to reduce the number of traffic accidents to zero, this study proves the government's efforts to address traffic safety issues on the road to be quite successful.